FORMULATION POLICY ON CRIMINAL PROVISION RELATED TO SEEDS ON FOOD SERTIFICATION - Sudjito, Bambang (Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThis research focuses on the formulation policy of criminal provisions related to seed certification which is based on the basis of farmersâ protection. The bases consideration in this research is the circumstance in which the policy of seed certification supported by the regulations supports the businessmen, instead of farmers. The impact of seed certification policy that is supported by related regulations is that farmersâ right as consumers in obtaining and utilizing qualified, certified, and labeled seeds (genetically, physiologically, and physically) is neglected. Furthermore, farmers obtain and utilize seeds from businessmen that do not comply with the quality set by the regulations. The goals of this research are as follows: (1) finding the factors of formulation policy on criminal provisions related to seed certification which is not based on farmersâ protection, (2) offering formulation policy which is related to farmer-based norms of criminal act of seed sertification protection, and (3) offering formulation policy which is related to farmer-based norms of criminal penalty of seed sertification protection. The hope into reality of this research, is formulating policy on criminal provision related to seed certification on the basis of farmersâ protection of plant cultivation through that values of justice, democracy, environmental awareness, and the sustainability. It is include of farmers protection as consumers to obtain and use qualified, certified, and labeled seeds (genetically, physiologically, and physically). .(Key words: formulation policy, criminal provisions, seed certification, and farmer-based protection)